Hardware Implementation and Control Strategy of Videoconference System Based on Rec. H.261 - 阎安; 姚晓靖; 刘万春; 石守义; 余松煜 (Tongxin xuebao)
The design and realization of a videoconference system based on international recommendations are introduced in this paper,whereas hardware implementation of video codec based on ITU-T H. 261 are briefly discussed, the transmission buffer control method and the adaptive quantization strategy are proposed.This system can be operated under the transmission rate from 128kb/s to 2Mb/s with system delay of about half a second and high subjective image quality.